2019
DOI: 10.1155/2019/4056436
|View full text |Cite
|
Sign up to set email alerts
|

Role of Functional Imaging Techniques to Assess Motor and Language Cortical Plasticity in Glioma Patients: A Systematic Review

Abstract: Cerebral plasticity is the ability of the central nervous system to reorganize itself in response to different injuries. The reshaping of functional areas is a crucial mechanism to compensate for damaged function. It is acknowledged that functional remodeling of cortical areas may occur also in glioma patients. Principal limits of previous investigations on cortical plasticity of motor and language functions included scarce reports of longitudinal evaluations and limited sample sizes. This systematic review is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 78 publications
(147 reference statements)
2
39
0
Order By: Relevance
“…Resting-state fMRI functional connectivity as well as new advanced HARDI (high angular resolution diffusion imaging) tractography methods are improving and reshaping the role of these advanced functional MRI techniques for surgery of gliomas [ 53 ], although larger studies are still warranted to encourage their wide clinical implementation in the near future. A promising application of functional imaging techniques in the assessment of cortical plasticity of motor and language functions in gliomas is currently a matter of investigation, especially to define how cognitive functional recovery or impairment is mirrored by specific imaging modifications, and to understand the association between longitudinal functional changes and progression of disease [ 55 ].…”
Section: Imagingmentioning
confidence: 99%
“…Resting-state fMRI functional connectivity as well as new advanced HARDI (high angular resolution diffusion imaging) tractography methods are improving and reshaping the role of these advanced functional MRI techniques for surgery of gliomas [ 53 ], although larger studies are still warranted to encourage their wide clinical implementation in the near future. A promising application of functional imaging techniques in the assessment of cortical plasticity of motor and language functions in gliomas is currently a matter of investigation, especially to define how cognitive functional recovery or impairment is mirrored by specific imaging modifications, and to understand the association between longitudinal functional changes and progression of disease [ 55 ].…”
Section: Imagingmentioning
confidence: 99%
“…Presurgical task-based/rsfMRI [ 46 ] and TMS [ 47 , 48 ] in glioma patients have first supported a local rearrangement of cortical motor representations, made possible thanks to a more complex and dynamic organization of the primary motor cortex than previously thought [ 49 ]. However, such a potential of local reshaping has limitations, since the motor system serves as a unimodal output, and then belongs to the “minimal common brain” (the neural structures with a low plastic potential) [ 50 ].…”
Section: The Contribution Of Fni and Tms Mapping To Investigate Inmentioning
confidence: 99%
“…A recent systematic review of eight studies comparing post- and preoperative brain activations in these two networks ( Cirillo et al, 2019 ) concluded that the motor function tends to reorganize mainly intrahemispherically, whereas language showed a wider reorganization potential. Results from the present review also suggest that the sensorimotor network reorganization may extend to the healthy hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…The current review aimed to provide a comprehensive overview of neuroplasticity in patients with glioma. With respect to previous reviews on the topic (e.g., Cirillo et al, 2019 ; Duffau, 2014 ), this review aimed to explore the extent of plasticity not only associated with glioma growth but also with surgery, the latter being more poorly explored. The studies we reviewed investigated plasticity under different aspects and by different methodologies.…”
Section: Relevant Research Questions Regarding Plasticity In Neuro-onmentioning
confidence: 99%